Influencia del ácido ascórbico, metabisulfito de sodio y sorbato de potasio en la conservación de una bebida de caña de azúcar - Bravo Vélez, Jasson Ramón (2022)
The purpose of this research was to evaluate the influence of ascorbic acid, sodium metabisulfite and potassium sorbate in the preservation of a drink made from the juice of the sugar cane (Saccharum officinarum) harvested at the “Mi Violetita” farm in the Tosagua canton by using a 23 factorial arrangement in a completely randomized design with three exact reproductions: also, by using 576L of sugarcane juice of the EC-03 variety as an experimental unit. Acidity, pH, ° Brix and color analyzes were carried out. The life cycle of the drink was performed by using the Labuza method. Acceptability was determined by a sensory test with non-professional tasters. These analyzes were accomplished during 30 days of storage, where days 0, 15 and 30 were evaluated. As results, pH values between 5.12 to 3.2 were obtained; °Brix from 18.5 to 21.2; titratable acidity (citric acid) between 0.34 and 0.87%, color from 269 to 972Hz; while T3 had a useful life of 5.8 days, with T5 being the one with the highest acceptance. The results obtained do not certify compliance with the Ecuadorian regulation NTE INEN 2304: 2017 because the highest amount of ° Brix is contemplated naturally in the raw material, in addition the useful lifetime was low because it was taken as a reference microorganism requirement of the regulation.